Response: Freedom from Pain as a Rawlsian Primary Good. (12th August 2016) - James Roberts, Adam
Abstract: In a recent article in this journal, Carl Knight and Andreas Albertsen argue that Rawlsian theories of distributive justice as applied to health and healthcare fail to accommodate both palliative care and the desirability of less painful treatments. The asserted Rawlsian focus on opportunities or capacities, as exemplified in Normal Daniels' developments of John Rawls' theory, results in a normative account of healthcare which is at best only indirectly sensitive to pain and so unable to account for the value of efforts of which the sole purpose is pain reduction. I argue that, far from undermining the Rawlsian project and its application to problems of health, what the authors' argument at most amounts to is a compelling case for the inclusion of freedom from physical pain within its index of primary goods.